PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 003 PASIR BONGKAL - Marlinda, Marlinda; Alpusari, Mahmud; Daud, Daman huri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: The problem in this research is in study IPS student still be very low, this proved by lowering reached nya KKM student, While KKM determined only 7 student people ( 35 %) which can reach KKM, while 13 people ( 65%) which don’t reach KKM determined, pursuant to the problem require to be searched by the road; street to solve problem among other things is represent more interesting study model with environmental condition in everyday life. Model study kontekstual put in the way of student to learn actively and please, entangling student consciously and also unconscious which can improve student ability and can apply it in life one day- class V SD Country student day 003 pasir bongkal teaching year 2015 with student amount 20 people . This research is done by 2 is cycle times;rill twice is meeting twice is daily restating. Instrument of data collecting of at this research is, student observation sheet, teacher observation sheet, and final tes restating of cycle . This research in the form of class research ( PTK), aim to to increase study IPS class V SD Country student 003 pasir bongkal of at items of gestation period independence .these result in dicate direct learning kontekstual model can improve study IPS ability, this is visible from elementary score improvement with mean 65,5 with category unable to, cycle I with mean 75,75 with category able to and at cycle II with mean 77,25 with category able to. this proven from elementary score mean result of cycle I and II improvement became of by cycle II that is cycle I 15,65% and cycle II 17,93% data result obtained improve to ability standard model.Keywords : learning kontekstual model, IPS